Dampak Penyalahgunaan Kekuasaan oleh Mantan Bupati Probolinggo: Studi Kasus Korupsi Jual Beli Jabatan - Bella Ola Shakira; Revalyza Misbah; Mega Arinda Pramessella; Zahra Hanifah Salma; Ridwan, Ridwan (JOSH: Journal of Sharia, 2025)
The case of buying and selling positions involving the former Regent of Probolinggo is one of the real portraits of abuse of power in local governance in Indonesia. This research aims to analyze the form of abuse of power committed by the former Regent of Probolinggo in the practice of buying and selling positions and its impact on local governance. This research uses a descriptive qualitative method with a literature study approach, using secondary data from previous research, media reports, news, academic literature related to corruption cases in the local government environment. The results show that the practice of buying and selling positions by public officials reflects a complex form of abuse of power, including abuse for personal gain, deviation from the purpose of the position, and violation of administrative procedures. These actions have a negative impact on the quality of the bureaucracy, reduce the efficiency of public services, and undermine public trust in government institutions. This case also shows the weakness of internal and external supervision, as well as the strong influence of transactional politics in appointments. This research recommends the importance of consistent law enforcement and strengthening the meritocracy based selection system to prevent future abuses of power. The limitation of this study is the use of secondary data, so further studies are recommended to use primary data to obtain a more in depth picture.